Pooled optical screening in bacteria using chromosomally expressed barcodes - Soares, Ruben R. G.; García-Soriano, Daniela A.; Larsson, Jimmy; Fange, David; Schirman, Dvir; Grillo, Marco; Knöppel, Anna; Chakra Sen, Beer; Svahn, Fabian; Zikrin, Spartak; Ratz, Michael; Nilsson, Mats; et al. (Uppsala University, 2025)
This data set contains code and data needed to generate the figures and tables presented in "Pooled optical screening in bacteria using chromosomally expressed barcodes". See link to the publication in Related Material.

Optical pooled screening is an important tool to study dynamic phenotypes for libraries of genetically engineered cells. However, the desired engineering often requires that the barcodes used for in situ genotyping are expressed from the chromosome. This has not previously been achieved in bacteria. Here we describe a method for in situ genotyping of libraries with genomic barcodes in Escherichia coli. The method is applied to measure the intracellular maturation time of 84 red fluorescent proteins.

All microscopy images and the corresponding image analysis code and outputs are found on the BioImage Archive. See link in Related Material.
Keywords: Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi